The Effect of Personality Traits And Financial Literation On Financial Behavior - Rahman, M. Auliya; Fauziyah, Azizah (The International Journal of Business Review (The Jobs Review), 2021)
The purpose of this study was to determine and analyze the influence of personality traits and financial literacy on financial behavior in young entrepreneurs of Micro, Small and Medium Enterprises (MSMEs) in Tasikmalaya City. The research method used is quantitative research methods. Data collection obtained through questionnaires, interviews, observation and literature study. The population in this study were 3,599 MSME Entrepreneurs in the City of Tasikmalaya. By using purposive sampling technique, the sample of this research is the beginner entrepreneurs of UMKM Kota Tasikmalaya who have just operated â‰¤ 5 years, as many as 30 entrepreneurs. The results of the study either partially or simultaneously, personality traits and financial literacy have a significant influence on financial behavior.